(untitled) (Journal of actual problems of jurisprudence, 2019)
In this article the author writes a review on the work of BA Zhumadilov who died prematurely. He believes that modern science Kazakh agrarian law has lost many of the new and original works that could be written Bakhyt Akadilovym, whether he is alive, to further his scienti fi c career, and in this respect, the Kazakhstan legal science has suffered a great, irreparable loss